A Study Of Personality And Body Esteem Of Healthy, Overweight, And Obese Adolescents (Journal of Pharmaceutical Negative Results, 2023)
The intent of the current research was to study the relationship between personality traits and body esteem among healthy, overweight, and obese adolescents. Healthy adolescents have body mass index (BMI) in the range of 17-24.9; overweight adolescents have body mass index in the range of 25-30 and obese adolescents have body mass index more than 30. Adolescence is a period of growth and changes both physically and psychologically. An overweight adolescent faces many challenges in his/her adolescent years because of various factors. Two such psychological factors are personality and body esteem, which have consequential effect on health-related issues. In the present study, a descriptive survey was conducted using Big Five Personality questionnaire and the Body Esteem scale which was administered among students studying in schools of Jaipur. Data analysis was done using IBM-SPSS software and the results were analyzed using correlation and one-way anova. Results revealed that negative emotionality was less exhibited by healthy adolescents as compared to overweight and obese adolescents. Extraversion, Agreeableness, conscientiousness, open-mindedness, and body esteem had significant relationship with the three groups. The present findings suggest that personality traits and body esteem of an adolescent play an important role in body mass index.